(untitled) (Gestión y Gerencia, 2018)
The sustainability of productivity growth in an economy is not only generated by the utilization level of production factors - capital and labor - but also by the efficiency increase in the use and combination of these factors. In this sense, this research analyzes credit productivity in SMI in the manufacturing sector of the state of Yaracuy, in order to demonstrate the efficiency of credit use by industries’ owners or managers and its relationship with searching of productivity, through the factors profitability in final goods. This is a field design descriptive study, which addressed nine industries in the footwear, textiles, clothing and metallurgical sectors. Relevant conclusion shows that the desired productivity was not generated by the granted financing, according with the production indicators and employment generation, due to the country’s economic environment and administrative barriers that significantly affected the industrial sector.